Java XML and JSON - Friesen, Jeff (Expert's voice in Java., 2016)
Java XML and JSON describes the popular XML and JSON data-interchange languages. You explore each language and learn how to parse/create XML-based documents and parse JSON-based documents via various Java APIs. You also learn how XML and JSON are used in AJAX (and AJAJ), Android, Big Data, and Web Services contexts, all from the Java perspective. What you'll learn How to use Java, JSON and XML together to build services, big data How to use XML; parse XML documents with SAX, DOM, StAX; selecting nodes with XPath; and transform XML documents with XSLT What is JSON and how to explore parsing JSON content with Google GSON, Jackson, Quick JSON How to roll your own JSON APIs How to use XML and JSON with Ajax, Android, big data and web services.